78‐4: Distinguished Paper: A 2.78‐in 1058‐ppi Ultra‐High‐Resolution Flexible OLED Display Using CAAC‐IGZO FETs. Issue 1 (May 2016) - Nagata, Takaaki; Hirasa, Shinich; Dozen, Yoshitaka; Jimbo, Yasuhiro; Yokoyama, Kohei; Hirakata, Yoshiharu; Yamazaki, Shunpei; Sato, Rai; Fujiwara, Chieko; Shiraishi, Takashi
Abstract : We have successfully fabricated a 2.78‐in 1058‐ppi flexible OLED display. This display exhibits the highest pixel density in the world among flexible displays using thin film transistors. The display can be bent with a curvature radius R = 1 mm and shows a high resistance.